2010
DOI: 10.1371/journal.pone.0012816
|View full text |Cite
|
Sign up to set email alerts
|

Degradation of p53 by Human Alphapapillomavirus E6 Proteins Shows a Stronger Correlation with Phylogeny than Oncogenicity

Abstract: BackgroundHuman Papillomavirus (HPV) E6 induced p53 degradation is thought to be an essential activity by which high-risk human Alphapapillomaviruses (alpha-HPVs) contribute to cervical cancer development. However, most of our understanding is derived from the comparison of HPV16 and HPV11. These two viruses are relatively distinct viruses, making the extrapolation of these results difficult. In the present study, we expand the tested strains (types) to include members of all known HPV species groups within th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
54
1
6

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 64 publications
(63 citation statements)
references
References 33 publications
2
54
1
6
Order By: Relevance
“…Growth characteristics were not related to the relatively small differences seen in transgene DNA copy numbers and expression levels. Overall, our Western blot results are in line with earlier reports showing p53 and pRb degradation by (probable) hrHPV types, but not by HPV11 (11)(12)(13)45). Similar to other in vitro studies (11,12), the p53 degradation capacities varied among the hrHPV types.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Growth characteristics were not related to the relatively small differences seen in transgene DNA copy numbers and expression levels. Overall, our Western blot results are in line with earlier reports showing p53 and pRb degradation by (probable) hrHPV types, but not by HPV11 (11)(12)(13)45). Similar to other in vitro studies (11,12), the p53 degradation capacities varied among the hrHPV types.…”
Section: Discussionsupporting
confidence: 92%
“…Furthermore, a large, randomized, controlled prospective trial conducted in the Netherlands has revealed that among hrHPV-positive women with normal cytology or borderline to moderate dyskaryosis, those infected with hrHPV types 16, 18, 31, and 33 have an increased 18-month risk of CIN3 or cancer (8). Apart from type-specific differences in viral persistence (9), these and other data also point to the existence of different oncogenic properties of the various high-risk types.Although some non-HPV16 and -18 types recently received some attention (11)(12)(13)(14), functional studies on transforming properties of hrHPV are mainly limited to HPV16 and HPV18. We and others have previously demonstrated that HPV16 and HPV18 can induce immortalization of primary human foreskin keratinocytes (HFKs) by successive bypass of two proliferative life span barriers, i.e., senescence and crisis (reviewed in reference 15).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The genome segment contained from the LCR to the E6 and E7 genes encodes oncoproteins described as essential for HPV-induced carcinogenesis in vivo 3 . E6 and E7 interact with tumor suppressor proteins p53 4 and pRB 5 , respectively, resulting in alteration of the DNA repair process and cell-cycle control.…”
Section: Introductionmentioning
confidence: 99%
“…Only recently have large-scale studies begun to investigate the p53 degradation activities of several E6 types (20,26). These studies provided important information as to which E6 types can promote the degradation of p53 in vitro, using in vitro-translated proteins (26), and in vivo, in transfected cells (20).…”
mentioning
confidence: 99%